1984
DOI: 10.3382/ps.0632384
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Food Restriction During Rearing on Fasting Heat Production of Layer Strain Pullets and Hens

Abstract: Fasting heat production was measured in darkened respiration chambers at three chronological and three physiological ages during rearing and laying in a layer strain to determine the effects of food restriction during rearing. There were three rearing treatments (42 to 162 days of age) in which birds were allowed ad libitum food intake (F) or were restricted by time (TR), in which birds were allowed continuous ad libitum food intake for about 24 hr in every 72 hr, or by proportion (PR), in which birds were off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Increased visit frequency is also a measure of locomotive activity, and increased locomotive activity increased ME m requirements ( van Kampen, 1976 , MacLeod et al., 1982 , MacLeod et al., 1988 ). Therefore, increased visit frequency could also be linked to increased HP ( Johnson and Farrell, 1984 ). A linear regression between HP and daily visit frequency up to week 21 showed that 1 extra visit per day corresponded to a 0.076 kcal increase in HP, after correcting for the fixed effects and interactions between BW treatment, photoschedule, and age ( P < 0.001; R 2 = 0.96; results not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Increased visit frequency is also a measure of locomotive activity, and increased locomotive activity increased ME m requirements ( van Kampen, 1976 , MacLeod et al., 1982 , MacLeod et al., 1988 ). Therefore, increased visit frequency could also be linked to increased HP ( Johnson and Farrell, 1984 ). A linear regression between HP and daily visit frequency up to week 21 showed that 1 extra visit per day corresponded to a 0.076 kcal increase in HP, after correcting for the fixed effects and interactions between BW treatment, photoschedule, and age ( P < 0.001; R 2 = 0.96; results not shown).…”
Section: Resultsmentioning
confidence: 99%
“…This statement does not discount work prior to these studies but is based on technological advancements and improved knowledge with regard to factors such as thermoneutral environment, acclimatisation and length of the period of measurement. Since the work of Brown (1965, 1967), a considerable number of reports have given details of the metabolic rates of appropriately starved poultry, hereafter referred to as starvation heat production (SHP) and of W. In addition, a large number of such measurements have been provided by studies on the SHP of pullets and laying hens as affected by undernutrition during rearing (Balnave^ a/., 1979; Johnson and Farrell, 1984).…”
Section: Origin Of Datamentioning
confidence: 98%
“…(1978) Balnave et al (1978) MacLeod and Shannon (1978) MacLeods al. (1979) Balnave et al (1979) Balnave et al (1979) Siregar and Farrell (1980 4 Johnson and Farrell (1983) Johnson and Farrell (1984) Johnson and Farrell (1984) Johnson and Farrell (unpublished) …”
mentioning
confidence: 95%